Perspektif Pengajar Dalam Implementasi Metode Maharah Qiro'ah Bagi Kru Garuda Indonesia Rute Timur Tengah - Dinnan Nadiyatul Fairuz; Faisal Hendra (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This study examines the implementation of teaching methods for Arabic reading skills (maharah qiro’ah) from the perspective of instructors in a training program for Garuda Indonesia crew members serving Middle Eastern routes. In this context, maharah qiro’ah encompasses the ability to read, comprehend, and accurately pronounce Arabic-language announcements and safety instructions. The study employs a descriptive qualitative approach, utilizing in-depth interviews with program instructors to uncover the strategies, challenges, and solutions involved in teaching Arabic for aviation-related professional purposes. Data were analyzed thematically to identify patterns in teaching practices. The findings indicate that instructors utilize a combination of direct, audio-lingual, communicative, and drill methods tailored to the specific needs of flight crew, with an emphasis on pronunciation accuracy and mastery of aviation-specific vocabulary. Approximately 70% of participants demonstrated significant improvement in their ability to read and pronounce Arabic texts following the program. Key challenges faced by instructors included the diversity of participants' backgrounds and initial proficiency levels, as well as the constraints of an intensive training schedule. This study offers conceptual and practical contributions to the development of Arabic teaching methodologies for specific purposes, particularly within the international aviation industry.